Bronchoscopic Journey of in vivo Real-Time Microscopic Imaging in ILD: A Case Series - Wijmans, Lizzy; Kalverda, Kirsten; de Bruin, Daniel; Brinkman, Paul; van den Berk, Inge; Roelofs, Joris J.T.H.; Jonkers, René; Bonta, Peter I.; Annema, Jouke (Respiration, 2022)
Background: Patients with interstitial lung diseases (ILDs) frequently present with nondiagnostic high-resolution CT (HRCT) scan and bronchoalveolar lavage (BAL) results, resulting in the need for invasive surgical or cryo-lung biopsy that is associated with significant morbidity. Confocal laser endomicroscopy (CLE) and optical coherence tomography (OCT) are high-resolution laser and light-based techniques that provide real-time imaging of the alveolar compartment during bronchoscopy with a different depth and field of view. Objectives: The aim of the study was to correlate OCT and CLE imaging to HRCT imaging in ILD. Methods: This is a retrospective case series of 20 ILD patients who underwent alveolar CLE and OCT imaging during a standard bronchoscopy with BAL, followed by a lung biopsy when indicated. CLE and OCT imaging were compared to four main HRCT patterns and histology. The final diagnosis was based on the multidisciplinary discussion diagnosis. Results: Bronchoscopic CLE and OCT imaging were feasible and safe and provided additional high-detailed anatomical information compared to the HRCT. Bronchoscopic real-time CLE was capable of identification of “alveolar cells” (ground glass opacities) and lung fibrosis (increased alveolar elastin fibers). Bronchoscopic real-time OCT allowed for visualization of “patchy fibrotic disease”, “honeycombing” (microcysts), and mucosal granulomas in the airways. Conclusions: Bronchoscopic CLE and OCT of the alveolar compartment is feasible and safe and enables minimally invasive, high-resolution detection of specific ILD features with the potential to improve ILD diagnostics and monitoring and decrease the need for surgical or cryo-lung biopsies.